Requirement Model for Instructor Management System - Lee, Ai Leng (2004)

(untitled)
The purpose of this project is to create a requirement model for Instructor Management System (IMS) based in Universiti Utara Malaysia (UUM), Kedah Darul Aman. Requirement model provide a more structured and integrated guide for the development of systems. Its serves as a good starting point or reference for system developers to understand the user's requirement which save cost, time and resources, thus helps to decrease effort in the system development process and increased quality of the developed system. The methodology for requirement mode of the IMS is derived from requirements, analyze requirements and validate requirement model. System modeling and prototyping approach were used for requirement validation, while HOORA Analysis Tool (HAT was used to validate the requirement model. Unified Modeling Language (UML) notation was adopted for the development of the requirement model. The requirement model consists of use case diagram, use case specification, class diagram, sequence diagram, collaboration diagram, activity diagram and supporting textual information. This requirement model provides a guideline in developing IMS by specifies a solution that is right for the user's needs. This project concludes by discussing problems and limitations that were encountered in completing this project, and offers a few recommendations for future development in this subject.